Karakteristik Pemerintah Daerah yang Mempengaruhi Belanja Pegawai, Belanja Barang, Belanja Hibah, dan Belanja Bantuan Sosial (Studi pada Kabupaten dan Kota di Wilayah Provinsi Jawa Tengah Tahun 2012) - Mustoffa, Ardyan Firdausi (Jurnal Ilmiah Cendekia Akuntansi; Vol 4 No 1 (2016): Jurnal Ilmiah Cendekia Akuntansi, 2018)
This research is aimed to analyze the factors that affect of the characteristics of the government local personnel expenditures,goods expenditures, grant expenditures and socialassistance expenditures in LKPD in Financial Report of Local Goverment 2012 in Central Java.The data used in this research is secondary data, namely the Local Government Finance Report in 2012 which has been audited by the Badan Pengawasan Keuangan Audit Report CPC in 35 districts / cities in Central Java province which was taken from the official website of the CPC. The analysis technique used in this research is the analysis of financial ratios and sample selection using purposive sampling method. The results of this study indicate that the variable size individually significant effect on personnel expenses. Variable independence ratio, the size of the board, the Human Development Index (HDI) and the status of individual regions no significant effect on personnel expenses. Variable size individually affect the expenditures goods. Variable independence ratio, the size of the board, the Human Development Index (HDI) and the status of the individual areas are not significant to the expenditures goods. Variable Ratio independence of the Human Development Index (HDI), Legislative Size, Size and Status individually not significant effect on grant expenditures. Status variable regions individually significant effect on social assistance expenditure ratio Independence Human Development Index, and the Legislative Size individually not significant effect on social assistance spending.